Glucagon-like peptide-2 enhances intestinal epithelial barrier function of both transcellular and paracellular pathways in the mouse. Issue 1 (1st July 2000) - Benjamin, M A; McKay, D M; Yang, P-C; Cameron, H; Perdue, M H
Abstract : BACKGROUND AND AIMS: Glucagon-like peptide-2 (GLP-2) is a recently identified potent intestinotrophic factor. We have evaluated the effect of GLP-2 treatment on intestinal epithelial barrier function in mice. METHODS: CD-1 mice were injected subcutaneously with GLP-2 or a protease resistant analogue, h[Gly 2 ]GLP-2, twice daily for up to 10 days. Saline injected mice served as controls. Jejunal segments were mounted in Ussing chambers. Tissue conductance was measured and unidirectional fluxes were determined for (i) Na + and the small inert probe Cr-EDTA (both transported via the paracellular pathway) and (ii) the macromolecule horseradish peroxidase (HRP, transported via the transcellular pathway). RESULTS: Mice treated with GLP-2 or h[Gly 2 ]GLP-2 for 10 days demonstrated significantly reduced intestinal conductance and fluxes of Na +, Cr-EDTA, and HRP. Electron microscopy confirmed that GLP-2 reduced endocytic uptake of HRP into enterocytes. Functional changes (evident by four hours) preceded morphological changes (evident by 48 hours). CONCLUSIONS: GLP-2 enhances intestinal epithelial barrier function by affecting both paracellular and transcellular pathways and thus may be of therapeutic value in a number of gastrointestinal conditions.